An unsteady squeezed flow of a tangent hyperbolic fluid over a sensor surface in the presence of variable thermal conductivity - K. Ganesh Kumar; B.J. Gireesha; M.R. Krishanamurthy; N.G. Rudraswamy (Results in Physics, 2017)
The paper explores the numerical study on squeezed flow of tangent hyperbolic fluid over a sensor surface with variable thermal conductivity. The governing equations are reassembling into ordinary non-linear differential equations by using suitable transformation and ensuing differential equations are solved numerically by RKF45 technique. The results of impartment parameter on velocity and temperature profiles are given diagrammatically. It is found that the variations of Weissenberg number, squeezed flow index parameter and permeable velocity parameter have strong influence on the momentum and thermal boundary layer thickness. Keywords: Squeezed flow, Tangent hyperbolic fluid, Variable thermal conductivity, Magnetic field